2018
DOI: 10.1017/s136898001700430x
|View full text |Cite
|
Sign up to set email alerts
|

A non-invasive assessment of skin carotenoid status through reflection spectroscopy is a feasible, reliable and potentially valid measure of fruit and vegetable consumption in a diverse community sample

Abstract: RS is a potentially improved method to approximate fruit and vegetable consumption among diverse participants. RS is portable and easy to use in field-based public health nutrition settings. More research is needed to investigate validity and sensitivity in diverse populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 29 publications
2
50
3
Order By: Relevance
“…Compared with the small number of other studies that have used the Veggie Meter™ technique, our mean CRS value of 346 is higher than that recorded in a diverse community sample in Eastern North Carolina USA of~240 in African American and Non-African American (n = 469) [21] and 57 from an eye clinic in Utah, USA [14] with mean CRS of 297, but similar to a Japanese study where the mean CRS was 342 [15]. While we show no significant difference in CRS between men and women, the Japanese [15] study demonstrated that Japanese women scored higher than men (382 vs. 315).…”
Section: Discussioncontrasting
confidence: 77%
“…Compared with the small number of other studies that have used the Veggie Meter™ technique, our mean CRS value of 346 is higher than that recorded in a diverse community sample in Eastern North Carolina USA of~240 in African American and Non-African American (n = 469) [21] and 57 from an eye clinic in Utah, USA [14] with mean CRS of 297, but similar to a Japanese study where the mean CRS was 342 [15]. While we show no significant difference in CRS between men and women, the Japanese [15] study demonstrated that Japanese women scored higher than men (382 vs. 315).…”
Section: Discussioncontrasting
confidence: 77%
“…The Veggie Meter® can be used easily in community‐based settings ( 14,15 ) . The Veggie Meter® has been validated against plasma carotenoids in a small sample of racially diverse adults ( 16 ) . Although RRS has been used in studies among 9–12 year old children to examine intervention effectiveness ( 11,12 ) , to our knowledge, no published studies have used the RS Device (the Veggie Meter®) in preschool and secondary school‐based settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that total carotenoid content was not associated with total fruit and vegetable servings is in line with previous research. Pitts et al noted a similar discrepancy among African Americans in North Carolina, such that while skin carotenoids were significantly associated with carotenoid intake and plasma carotenoids, they were not associated with total self-reported fruit and vegetable intake (excluding potatoes) [19]. These findings highlight that specific messages focused on increasing red, orange, and dark green vegetables may be necessary to increase the intake of carotenoid-rich produce.…”
Section: Discussionmentioning
confidence: 89%